Prevalencia de úlcera gástrica en cerdos faenados en el camal municipal del cantón Machala - Abril Salazar, Juan Carlos (2014)
The research was carried out in the Municipal Slaughterhouse Canton Machala, from December 10, 2012 to February 7, 2013, in order to determine the prevalence of gastric ulcers in pigs are slaughtered in the above listing, for this the following objectives and obtained the following results, the rate of prevalence of gastric ulcer that was obtained is 5.24%, also found that there was increased susceptibility of males to suffer the disease than in the female with regard sex, with regard to the provenance was established in Tenguel and Balsas are the counties with the highest prevalence of gastric ulcer, and with regard to the location of the ulcer all positive cases was obtained in the cardial region stomachs inspected, with respect to power a large percentage of this pathology positive animals were fed with concentrated.